First sight at entomotoxicology using Peckia intermutans (Diptera: Sarcophagidae) in Ecuador and its potential as a marker for methanol determination in biological samples - RIVERA-PUMA, Celia C. (2024)
. Forensic entomotoxicology, which analyzes necrophagous insects to detect toxic substances, is crucial in determining causes of death and estimating the post-mortem interval. This study focused on Peckia intermutans (Walker) (Diptera: Sarcophagidae) as a marker for detecting methanol, a potentially lethal alcohol often added as an adulterant in alcoholic beverages due to its low cost and similarity to ethanol. A gas chromatography-mass spectrometry (HS-GC-MS) method was developed to detect methanol, and its effects on the development time, survival, and morphology of flesh flies were investigated. Larvae were reared on liver substrates enriched with methanol (300, 500, and 1000 mg/kg). Results showed: the developed method detected methanol in all instars; methanol affected the developmental time of the flies; survival increased with higher methanol concentration; and morphological changes were evident in weight. This study provides valuable information on entomotoxicological research in Ecuador, emphasizing the need to consider morphological changes in P. intermutans to avoid inaccurate estimations of post-mortem intervals